(untitled) (Dhaka University Journal of Biological Sciences, 2017)
An experiment was conducted during T. Aman 2010 and Boro 2010-11 seasons to determine the effect of industrial effluents on seed germination and seedling growth of rice. In both the seasons, all the effluents and city waste water (CWW) had no effect on rice seed germination except pharmaceutical effluent. Pharmaceutical effluent showed the lowest seed germination. City waste water gave the highest shoot length (8.40 and 5.38 cm) and root length (8.06 and 6.35 cm) in the T. Aman and Boro seasons, respectively. Pharmaceutical effluent gave the highest shoot-root ratio of 10.49 while tannery effluent gave lowest ratio of 0.91. In both T. Aman and Boro seasons, seedling weight with and without endosperm, seedlings dry weight, seedling strength were found higher with CWW. During T. Aman and Boro seasons, relative germination ratio showed higher with a beverage effluent but relative shoot and root elongation ratio were found higher with CWW managed treatment. Dhaka Univ. J. Biol. Sci. 26(1): 59-68, 2017 (January)